Effect of aza-BODIPY-photodynamic therapy on the expression of carcinoma-associated genes and cell death mode - Elgun, Tugba; Yurttas, Asiye Gok; Cinar, Kamil; Ozcelik, Sennur; Gul, Ahmet (Elsevier, 2023)
Background: Breast cancer is the most common cancer affecting women worldwide.Photodynamic therapy(PDT) has now proven to be a promising form of cancer therapy due to its targeted and low cytotoxicity to healthy cells and tissues.PDT is a technique used to create cell death localized by light after application of a light-sensitive agent.Aza-BODIPY is a promising photosensitizer for use in PDT. Our results showed that aza-BODIPY-PDT induced apoptosis, probably through p53 and caspase3 in MCF-7 cells. Future studies should delineate the molecular mechanisms underlying aza-BODIPY-PDT-induced cell death for a better understanding of the signaling pathways modulated by the therapy so that this novel technology could be implemented in the clinic for treating breast cancer.Aim: In this study,we aimed to determine the change in the expression levels of 88 carcinoma-associated genes induced by aza-BODIPY-PDT were analyzed so as to understand the specific pathways that are modulated by aza-BODIPY-PDT. Material method: In this study,the molecular basis of the anti-cancer activity of aza-BODIPY-PDT was investi-gated.Induction of apoptosis and necrosis in MCF-7 breast cancer cells after treatment with aza-BODIPY de-rivative with phthalonitrile substituents (aza-BODIPY) followed by light exposure was evaluated by Annexin V 7-Aminoactinomycin D (7-AAD) flow cytometry.Results: Aza-BODIPY-PDT induced cell death in MCF-7 cells treated with aza-BODIPY-PDT; flow cytometry revealed that 28 % of the cells died by apoptosis. Seven of the 88 carcinoma-associated genes that were assayed were differentially expressed -EGF, LEF1, WNT1, TCF7, and TGFBR2 were downregulated, and CASP3 and TP53 were upregulated - in cells subjected to aza-BODIPY-PDT.This made us think that the aza-BODIPY-PDT induced caspase 3 and p53-mediated apoptosis in MCF7 cells.Conclusion: In our study,it was determined that the application of aza-BODIPY-PDT to MCF7 cells had a negative effect on cell connectivity and cell cycle.The fact that the same effect was not observed in control cells and MCF7 cells in the dark field of aza-BODIPY indicates that aza-BODIPY has a strong phodynamic anticancer effect.
Keywords: Photodynamic therapy; MCF7 cancer cell; Aza-BODIPY-PDT; Gene expression